Rock salt type high-entropy oxide for glucose sensor

By using rock salt-type high-entropy oxide (Mg0.2Co0.2Ni0.2Cu0.2Zn0.2)O as a modified electrode material in an enzyme-free glucose sensor, the problem of insufficient sensitivity of CuO, CoO and NiO is solved, and the sensitivity of the sensor is improved and cycle stability, achieving more efficient glucose detection.

CN119198848APending Publication Date: 2024-12-27CHENGDU UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411355481.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing enzyme-free glucose sensors are insufficient in sensitivity when using CuO, CoO, and NiO, and the dense copper-cobalt coating leads to a low effective active area, affecting catalytic performance.

Method used

Rock salt-type high-entropy oxide (Mg0.2Co0.2Ni0.2Cu0.2Zn0.2)O is used as the sensor-modified electrode material, and is prepared by sol gel and calcination method, combined with Nafion solution and ultrasonic treatment to improve the sensitivity and anti-interference of the electrode. ability.

Benefits of technology

The sensitivity of glucose sensors is improved, the cycle stability is enhanced, and the detection range is expanded, which avoids the problems of low sensitivity and insufficient active sites of monometallic active substances, and provides a more efficient charge transport pathway.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119198848A_ABST
    Figure CN119198848A_ABST
Patent Text Reader

Abstract

The invention relates to the field of glucose sensors, in particular to a rock salt type high-entropy oxide for enzyme-free glucose sensor active substances. The high-entropy oxide is of a single-phase rock salt structure, the molecular formula is MO, and M in the formula is composed of five transition metal elements including Cu, Co, Ni and any two of Mn, Zn, Mg and Fe. According to the preparation method, Mg, Co, Ni, Cu and Zn are preferably selected, and the (MgCoNiCuZn) O high-entropy oxide is prepared through a sol-gel and roasting method. The high-entropy oxide is selected as an active substance to prepare the glucose sensor, and the glucose sensing performance of the glucose sensor is as follows: the sensitivity in a linear range of 5-400 [mu] M is 108.14 [mu] AmM <-1 > cm <-2 >, the sensitivity in a linear range of 400-1500 [mu] M is 41.84 [mu] AmM <-1 > cm <-2 >, and the lower detection limit is 0.3 [mu] M. The high-entropy oxide is applied to the enzyme-free glucose sensor, and the electrode material is simple to prepare, low in cost, high in sensitivity, wide in linear range and good in application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a rock salt type high entropy oxide for a glucose sensor, belonging to the field of glucose sensors. Background Art

[0002] Diabetes is a common and frequent disease worldwide. The complications it may cause are extremely dangerous (such as heart disease, kidney failure, blindness, etc.), making it second only to cardiovascular disease and cancer in terms of risk. At present, the core means of treating diabetes is that patients need to frequently monitor their blood sugar and inject an appropriate amount of insulin to maintain blood sugar within the normal range of 4 to 6.6 mM (80 to 120 mg), thereby effectively reducing or avoiding the occurrence of complications. Therefore, the development of a blood sugar detection tool with high sensitivity, good selectivity and ease of use is of great significance for the diagnosis and treatment of diabetes.

[0003] The core component of blood sugar testing tools is the glucose sensor, which includes enzyme glucose sensors and non-enzyme glucose sensors. Among them, although enzyme sensors are accurate, they are expensive and have strict experimental conditions. Therefore, non-enzyme glucose sensors have received extensive research attention in recent years.

[0004] The common electrode materials of non-enzymatic glucose sensors include carbon materials, precious metal materials, transition metal oxide materials and their composites. Among them, transition metal oxides have the characteristics of high stability, low cost and simple synthesis process. The special outer electron structure of copper, cobalt and nickel in transition metals makes them have high catalytic performance for glucose.

[0005] In the early days, the direct use of single metal oxides as glucose sensors would result in poor sensing performance due to the single active substance and insufficient effective active area, so researchers used composite materials to solve this problem. Metal heterojunctions can make materials have higher conductivity and electrochemical activity. For example, patent CN202111149943.7 discloses a method for preparing a bimetallic organic framework enzyme-free glucose sensor. By adjusting the ratio of Co and Zn elements in ZIF67 / ZIF8, hybrid transition metal-based compounds show excellent performance in the field of enzyme-free glucose sensing. Compared with single metal organic frameworks, the electrocatalytic performance of bimetallic organic frameworks for glucose has been improved.

[0006] Using multi-metal oxides as active substances, when the sensor is working, each metal is converted into the corresponding oxyhydroxide, and glucose is catalyzed and oxidized at the same time. Aydan Zeynalova et al. (A. Zeynalova, KOOskay, Cost-Effective and Fast Fabrication of Copper–Cobalt Electrochemical Glucose Sensor, Journal of Electronic Materials, 52 (2023) 6791-6799) developed porous copper-cobalt coatings and porous copper coatings through one-step electrodeposition technology. Through cyclic voltammetry tests, it was found that the catalytic performance of the copper-cobalt coating was better. In the linear ranges of 20μM-1mM and 1mM-7.5mM, the sensitivity was 6.5μA mM respectively. -1 cm -2 and 0.64 μA mM -1 cm -2 , the detection limit is 2.8μM. The one-step electrodeposition method adopted in this technical solution is low-cost and high-efficiency. The principles of cobalt and copper are similar. In the process of glucose detection, they are first oxidized to cobalt hydroxide oxide and then oxidized to glucose. However, due to the electrodeposition method, the copper-cobalt coating is dense and has a low effective active area. In addition, during the catalytic process, copper-cobalt needs to be oxidized to copper oxide and cobalt oxide first, and then oxidized to hydroxide oxide before it can catalyze the oxidation of glucose, which will significantly reduce the sensitivity of the sensor.

[0007] Continue to increase the number of types of metal oxides. It is known that oxides of transition metals cobalt, nickel, and copper with high catalytic activity are difficult to form single-phase materials and easily generate mixed phases. Therefore, high-entropy materials composed of five or more metal elements can be used as active substances.

[0008] High entropy materials are single-phase materials composed of five or more elements in equimolar or nearly equimolar ratios. Compared with catalysts composed of a single or small amount of elements, high entropy materials have higher configurational entropy and more disordered chemical composition and atomic distribution, and their thermodynamic and kinetic properties are excellent. Among them, high entropy oxides are more easily combined with active metals. As catalysts, high entropy oxides have good versatility, controllability of component design and stability, which play an important role in improving catalytic efficiency. R. Zhang et al. (R. Zhang, Z. Xu, et al. Electrodeposition of Self-Supported High-Entropy Spinel Oxides for Stable Oxygen Evolution. [J]. Inorganic Chemistry, 62 (2023) 19052-19059.) used a rapid two-step method to prepare self-supporting high-entropy spinel oxides on carbon cloth-(Fe 0.2 Co 0.2 Ni 0.2 Mn 0.2 Cr 0.2 ) 3 O 4 @CC is used to catalyze the oxygen evolution reaction, requiring only an overpotential of 287 mV and having excellent cycle stability. Lin H et al. (Lin H, Jiabin Z, et al. Efficient removal of tetracycline hydrochloride by high entropy oxides in visible photo-Fenton catalytic process. [J]. Environmental technology, 2023, 41-46.) synthesized a high entropy oxide (Mn) with a spinel structure. 0.2 Fe 0.2 Co 0.2 Ni 0.2 Cu 0.2 ) 3 O 4 (MFO) composite materials were first used in the photocatalytic degradation of antibiotic organic pollutants in water, and they have high catalytic removal ability for tetracycline hydrochloride. As mentioned above, high entropy oxides are widely used to accelerate the catalytic process. However, there is no precedent for applying high entropy oxides to glucose sensors, and the sensing performance of various high entropy oxides for glucose is still unknown.

[0009] In summary, given the advantages of high entropy materials, the application of high entropy oxides in the field of enzyme-free glucose sensors is possible. Rock salt-type high entropy oxides can be used to improve the sensitivity, detection range and anti-interference ability of enzyme-free glucose sensor modified electrodes, and to develop simpler, more reliable and practical enzyme-free glucose sensors, which have great technical value and application prospects. Summary of the invention

[0010] In view of the problem that CuO, CoO and NiO are insufficiently sensitive when used as glucose sensors, the present invention provides a rock salt type high entropy oxide for glucose sensors.

[0011] The present invention designs a single-phase rock salt structure high entropy oxide, the molecular formula is MO, wherein M is composed of five transition metal elements, including Cu, Co, Ni, and any two of Mn, Zn, Mg, and Fe. Preferably, the metal elements include Mg, Co, Ni, Cu, and Zn, and the five transition metal nitrates are used as raw materials to prepare (Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 )O rock salt type high entropy oxide, the metal atomic ratio is 1:1:1:1:1, and the chemical formula is abbreviated as (MgCoNiCuZn)O.

[0012] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is:

[0013] MO rock salt type high entropy oxide uses five metal nitrate hydrates as metal ion sources, including cobalt nitrate hexahydrate, nickel nitrate hexahydrate, copper nitrate trihydrate, and any two of manganese nitrate tetrahydrate, zinc nitrate hexahydrate, magnesium nitrate hexahydrate, and iron nitrate nonahydrate, and monohydrated citric acid as a chelating agent. MO rock salt type high entropy oxide is prepared by sol-gel and calcination methods.

[0014] The method for preparing the MO rock salt type high entropy oxide specifically comprises the following steps:

[0015] Step 1, preparation of a gel precursor, weigh 3 mmol of five selected metal nitrate hydrates in equimolar ratios, dissolve them to obtain a mixed solution with a metal cation concentration of 0.3 mol / L, heat the mixed solution to 90°C under stirring, add 3.5 g of citric acid monohydrate, continue stirring and heating at 90°C for 1 hour to form a sol, and then dry at 80°C for 12 hours to obtain a gel precursor.

[0016] Step 2, calcining to prepare oxides. The gel prepared in step 1 is not ground, but placed in a corundum crucible in the form of uneven blocks, and then calcined at 900° C. for 4 hours and cooled in the furnace to obtain MO rock salt type high entropy oxides.

[0017] In step 2, the purpose of not grinding the gel precursor is to prevent the gel from decomposing and generating gas to carry out powder during the calcination process.

[0018] A preparation method of an enzyme-free glucose sensor based on MO rock salt type high entropy oxide, comprising the following steps: dispersing 4 mg of MO in a mixed solution of 490 μL of deionized water and 500 μL of anhydrous ethanol, dropping 10 μL of Nafion solution and ultrasonicating for 30 min to obtain a suspension, dropping a certain volume of the suspension on a glassy carbon electrode, drying at room temperature and then dropping an equal volume of the suspension on the glassy carbon electrode again, and then drying at room temperature to obtain an enzyme-free glucose sensor based on MO rock salt type high entropy oxide, referred to as MO / GCE.

[0019] In the method for preparing the enzyme-free glucose sensor, the volume of the suspension applied twice on the glassy carbon electrode is 5 μL.

[0020] A method for detecting glucose using a MO-based enzyme-free glucose sensor comprises the following steps:

[0021] Step a, cyclic voltammetry test, using a three-electrode system, a scan rate of 30 mV / s, a voltage range of -0.2 v to 0.6 v, MO / GCE was placed in 0.1 M NaOH solution with 0 mM, 0.2 mM, 0.4 mM, and 0.6 mM glucose concentrations, respectively, to obtain cyclic voltammetry curves at different glucose concentrations.

[0022] Step b, time-current titration curve test, MO / GCE is placed in 0.1M NaOH solution, and under working voltage conditions, glucose of known concentration is dripped every 50s to perform current response detection to obtain the IT curve, and the obtained current value is fitted with the corresponding glucose concentration to obtain a linear relationship curve between glucose concentration and response current.

[0023] In the step b, the operating voltage is 0.5V.

[0024] The beneficial effects of the present invention are as follows:

[0025] XRD test shows that the synthesized MO rock salt type high entropy oxide is a single-phase material without interference from other oxide impurities;

[0026] The high entropy effect of MO ensures the stability of the phase and improves the cycle stability and repetition rate of the glucose sensor. The cocktail effect combines the glucose catalytic performance of CoO, NiO, and CuO, avoiding the shortcomings of low sensitivity and too few active sites of single metal active substances.

[0027] The complex arrangement of metal atoms in MO can produce more efficient charge transfer pathways, increase the overall charge transfer rate, and contribute to the improvement of sensitivity;

[0028] High entropy oxides are used as active materials to provide new materials for the preparation of active materials for glucose sensors. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is the XRD spectrum of the (MgCoNiCuZn)O rock salt type high entropy oxide prepared in Example 1.

[0030] Figure 2 1 is the cyclic voltammetry curve of the (MgCoNiCuZn)O / GCE glucose sensor prepared in Example 1 at different glucose concentrations.

[0031] Figure 3 This is the time-current titration curve of the (MgCoNiCuZn)O / GCE glucose sensor prepared in Example 1.

[0032] Figure 4 yes Figure 3 Fitting curve within the linear range of the time-current curve. DETAILED DESCRIPTION

[0033] The present invention is further described in detail through embodiments and in conjunction with the accompanying drawings.

[0034] Example 1

[0035] To prepare a gel precursor, 0.3 mmol of magnesium nitrate hexahydrate, cobalt nitrate hexahydrate, nickel nitrate hexahydrate, copper nitrate trihydrate, and zinc nitrate hexahydrate were weighed in equal molar ratios and dissolved in deionized water to prepare a mixed solution with a metal cation concentration of 0.3 mol / L. Heat the mixed solution to 90°C under stirring, and add 3.5 g of citric acid monohydrate to the mixed solution. The sol obtained by continuous stirring and heating at 90°C was dried at 80°C for 12 hours to obtain a gel precursor. The oxide was prepared by high-temperature calcination. The gel was not ground and placed in a corundum crucible in an uneven block, and then calcined at 900°C for 4 hours to obtain (MgCoNiCuZn)O rock salt type high entropy oxide.

[0036] To prepare an enzyme-free glucose sensor based on (MgCoNiCuZn)O, 4 mg of (MgCoNiCuZn)O was dispersed in a mixed solution of 490 μL deionized water and 500 μL anhydrous ethanol, and 10 μL of Nafion solution was added and ultrasonicated for 30 min to obtain a suspension. 5 μL of the suspension was drop-coated on a glassy carbon electrode, dried at room temperature, and then the same volume of the suspension was drop-coated on the glassy carbon electrode again, and then dried at room temperature to obtain an enzyme-free glucose sensor based on (MgCoNiCuZn)O, referred to as (MgCoNiCuZn)O / GCE.

[0037] Cyclic voltammetry test was used to preliminarily detect the response effect of (MgCoNiCuZn)O / GCE to glucose. Using a three-electrode system, the scan rate was 30mv / s, and the voltage range was -0.2v to 0.6v. (MgCoNiCuZn)O / GCE was placed in 0.1M NaOH solution with 0mM, 0.2mM, 0.4mM, and 0.6mM glucose concentrations for cyclic voltammetry test.

[0038] Time-current titration curve test: (MgCoNiCuZn)O / GCE was placed in 0.1M NaOH solution, and glucose of known concentration was dripped into it every 50s under 0.5V voltage condition to obtain the IT curve. The obtained current value was fitted with the corresponding glucose concentration to obtain the linear relationship curve between glucose concentration and response current. The specific glucose concentration during the titration process is shown in Table 1.

[0039] Table 1 Glucose concentration detected by (MgCoNiCuZn)O / GCE at different times

[0040] Time(s) Glucose concentration in solution (μM) Time(s) Glucose concentration in solution (μM) 350 5 850 150 400 10 900 200 450 15 950 300 500 20 1000 400 550 30 1050 600 600 40 1100 800 650 50 1150 1000 700 60 1200 1500 750 80 1250 2000 800 100 1300 2500

[0041] The synthesized (MgCoNiCuZn) OXRD test results ( Figure 1 ) indicates that it is a single-phase material without interference from other oxide impurities.

[0042] The prepared (MgCoNiCuZn)O / GCE showed no obvious redox peak in the cyclic voltammetry test when glucose was not added. However, after glucose was added, an obvious Faraday current ( Figure 2 ), corresponding to the irreversible oxidation of glucose, indicating that (MgCoNiCuZn)O / GCE has good sensing performance for glucose and good detection sensitivity. The time-current titration curve of the sensor ( Figure 3 ) can obtain the linear fitting curve of glucose concentration and response current ( Figure 4), the calculation results show that the sensitivity of the (MgCoNiCuZn)O / GCE sensor for glucose detection is 108.14μAmM in the linear range of 5-400μM -1 cm -2 , the sensitivity is 41.84μAmM in the linear range of 400-1500μM -1 cm -2 The detection limit was 0.3 μM.

[0043] Example 2

[0044] To prepare a gel precursor, weigh 0.3 mmol of magnesium nitrate hexahydrate, cobalt nitrate hexahydrate, nickel nitrate hexahydrate, copper nitrate trihydrate, and zinc nitrate hexahydrate in an equimolar ratio and dissolve them in deionized water to prepare a mixed solution with a metal cation concentration of 0.3 mol / L. Heat the mixed solution to 90°C under stirring, and add 3.5 g of citric acid monohydrate to the mixed solution. The sol obtained by continuous stirring and heating at 90°C is dried at 80°C for 12 hours to obtain a gel precursor. The oxide is prepared by high-temperature calcination. The gel is not ground and placed in a corundum crucible in an uneven block. It is then calcined at 900°C for 5 hours to obtain (MgCoNiCuZn)O-5h rock salt type high entropy oxide.

[0045] To prepare an enzyme-free glucose sensor based on (MgCoNiCuZn)O-5h, 4 mg of (MgCoNiCuZn)O-5h was dispersed in a mixed solution of 490 μL deionized water and 500 μL anhydrous ethanol, and 10 μL of Nafion solution was added and ultrasonicated for 30 min to obtain a suspension. 5 μL of the suspension was drop-coated on a glassy carbon electrode, dried at room temperature, and then the same volume of the suspension was drop-coated on the glassy carbon electrode again, and then dried at room temperature to obtain an enzyme-free glucose sensor based on (MgCoNiCuZn)O-5h.

[0046] Example 3

[0047] To prepare a gel precursor, 0.3 mmol of magnesium nitrate hexahydrate, cobalt nitrate hexahydrate, nickel nitrate hexahydrate, copper nitrate trihydrate, and zinc nitrate hexahydrate were weighed in an equimolar ratio and dissolved in deionized water to prepare a mixed solution with a metal cation concentration of 0.3 mol / L. Heat the mixed solution to 90°C under stirring, and add 3.5 g of citric acid monohydrate to the mixed solution. The sol obtained by continuous stirring and heating at 90°C was dried at 80°C for 12 hours to obtain a gel precursor. The oxide was prepared by high-temperature calcination. The gel was not ground and placed in a corundum crucible in an uneven block, and then calcined at 900°C for 3 hours to obtain (MgCoNiCuZn)O-3h rock salt type high entropy oxide.

[0048] To prepare an enzyme-free glucose sensor based on (MgCoNiCuZn)O-3h, 4 mg of (MgCoNiCuZn)O-3h was dispersed in a mixed solution of 490 μL deionized water and 500 μL anhydrous ethanol, and 10 μL of Nafion solution was added and ultrasonicated for 30 min to obtain a suspension. 5 μL of the suspension was drop-coated on a glassy carbon electrode, dried at room temperature, and then the same volume of the suspension was drop-coated on the glassy carbon electrode again, and then dried at room temperature to obtain an enzyme-free glucose sensor based on (MgCoNiCuZn)O-3h.

[0049] Example 4

[0050] To prepare a gel precursor, 0.3 mmol of magnesium nitrate hexahydrate, cobalt nitrate hexahydrate, nickel nitrate hexahydrate, copper nitrate trihydrate, and zinc nitrate hexahydrate were weighed in equal molar ratios and dissolved in deionized water to prepare a mixed solution with a metal cation concentration of 0.3 mol / L. Heat the mixed solution to 90°C under stirring, and add 3.5 g of citric acid monohydrate to the mixed solution. The sol obtained by continuous stirring and heating at 90°C was dried at 80°C for 12 hours to obtain a gel precursor. The oxide was prepared by high-temperature calcination. The gel was not ground and placed in a corundum crucible in an uneven block, and then calcined at 800°C for 4 hours to obtain (MgCoNiCuZn)O-800 rock salt type high entropy oxide.

[0051] To prepare the enzyme-free glucose sensor based on (MgCoNiCuZn)O-800, 4 mg of (MgCoNiCuZn)O-800 was dispersed in a mixed solution of 490 μL deionized water and 500 μL anhydrous ethanol, and 10 μL of Nafion solution was added and ultrasonicated for 30 min to obtain a suspension. 5 μL of the suspension was drop-coated on a glassy carbon electrode, dried at room temperature, and then an equal volume of the suspension was drop-coated on the glassy carbon electrode again, and then dried at room temperature to obtain an enzyme-free glucose sensor based on (MgCoNiCuZn)O-800.

[0052] Example 5

[0053] To prepare a gel precursor, 0.3 mmol of magnesium nitrate hexahydrate, cobalt nitrate hexahydrate, nickel nitrate hexahydrate, copper nitrate trihydrate, and zinc nitrate hexahydrate were weighed in equal molar ratios and dissolved in deionized water to prepare a mixed solution with a metal cation concentration of 0.3 mol / L. Heat the mixed solution to 90°C under stirring, and add 3.5 g of citric acid monohydrate to the mixed solution. The sol obtained by continuous stirring and heating at 90°C was dried at 80°C for 12 hours to obtain a gel precursor. The oxide was prepared by high-temperature calcination. The gel was not ground and placed in a corundum crucible in an uneven block, and then calcined at 1000°C for 4 hours to obtain (MgCoNiCuZn)O-1000 rock salt type high entropy oxide.

[0054] To prepare the enzyme-free glucose sensor based on (MgCoNiCuZn)O-1000, 4 mg of (MgCoNiCuZn)O-1000 was dispersed in a mixed solution of 490 μL deionized water and 500 μL anhydrous ethanol, and 10 μL of Nafion solution was added and ultrasonicated for 30 min to obtain a suspension. 5 μL of the suspension was drop-coated on a glassy carbon electrode, dried at room temperature, and then an equal volume of the suspension was drop-coated on the glassy carbon electrode again, and then dried at room temperature to obtain an enzyme-free glucose sensor based on (MgCoNiCuZn)O-1000.

[0055] Example 6

[0056] To prepare a gel precursor, 0.3 mmol of ferric nitrate nonahydrate, cobalt nitrate hexahydrate, nickel nitrate hexahydrate, copper nitrate trihydrate, and zinc nitrate hexahydrate were weighed in equal molar ratios and dissolved in deionized water to prepare a mixed solution with a metal cation concentration of 0.3 mol / L. Heat the mixed solution to 90°C under stirring, and add 3.5 g of citric acid monohydrate to the mixed solution. The sol obtained by continuous stirring and heating at 90°C was dried at 80°C for 12 hours to obtain a gel precursor. The oxide was prepared by high-temperature calcination. The gel was not ground and placed in a corundum crucible in an uneven block, and then calcined at 900°C for 4 hours to obtain (FeCoNiCuZn)O rock salt type high entropy oxide.

[0057] To prepare an enzyme-free glucose sensor based on (FeCoNiCuZn)O, 4 mg of (FeCoNiCuZn)O was dispersed in a mixed solution of 490 μL deionized water and 500 μL anhydrous ethanol, and 10 μL of Nafion solution was added and ultrasonicated for 30 min to obtain a suspension. 5 μL of the suspension was drop-coated on a glassy carbon electrode, dried at room temperature, and then an equal volume of the suspension was drop-coated on the glassy carbon electrode again, and then dried at room temperature to obtain an enzyme-free glucose sensor based on (FeCoNiCuZn)O.

[0058] Example 7

[0059] To prepare a gel precursor, 0.3 mmol of manganese nitrate tetrahydrate, cobalt nitrate hexahydrate, nickel nitrate hexahydrate, copper nitrate trihydrate, and zinc nitrate hexahydrate were weighed in equal molar ratios and dissolved in deionized water to prepare a mixed solution with a metal cation concentration of 0.3 mol / L. Heat the mixed solution to 90°C under stirring, and add 3.5 g of citric acid monohydrate to the mixed solution. The sol obtained by continuous stirring and heating at 90°C was dried at 80°C for 12 hours to obtain a gel precursor. The oxide was prepared by high-temperature calcination. The gel was not ground and placed in a corundum crucible in an uneven block, and then calcined at 900°C for 4 hours to obtain (MnCoNiCuZn)O rock salt type high entropy oxide.

[0060] To prepare the enzyme-free glucose sensor based on (MnCoNiCuZn)O, 4 mg of (MnCoNiCuZn)O was dispersed in a mixed solution of 490 μL deionized water and 500 μL anhydrous ethanol, and 10 μL of Nafion solution was added and ultrasonicated for 30 min to obtain a suspension. 5 μL of the suspension was drop-coated on a glassy carbon electrode, dried at room temperature, and then the same volume of the suspension was drop-coated on the glassy carbon electrode again, and then dried at room temperature to obtain an enzyme-free glucose sensor based on (MnCoNiCuZn)O.

[0061] The above description is only a specific embodiment of the present invention, and does not limit the scope of the patent of the present invention. Without departing from its principle, modifications and improvements to the present invention and direct or indirect use of the related technologies of the present invention are all included in the patent protection scope of the present invention.

Claims

1. A rock salt type high entropy oxide for a glucose sensor, characterized in that: The high entropy oxide is a single-phase rock salt structure and is applied to enzyme-free glucose sensors.

2. The rock salt type high entropy oxide according to claim 1, characterized in that: The molecular formula is MO, wherein M is composed of five transition metal elements in an atomic ratio of 1:1:1:1:1, including any two of Cu, Co, Ni, and Mn, Zn, Mg, and Fe.

3. According to the rock-salt high entropy oxide according to claim 1 or 2, the metal elements preferably include Mg, Co, Ni, Cu, and Zn, the metal atomic ratio is 1:1:1:1:1, and the chemical formula is (MgCoNiCuZn)O.

4. The use according to claim 1, characterized in that The sensitivity of rock salt high entropy oxide in the linear range of glucose concentration of 5-400 μM is 108.14 μAmM -1 cm -2 , the sensitivity in the linear range of 400-1500μM is 41.84μAmM - 1 cm -2 , the detection limit was 0.3 μM.

Citation Information

Cited By

  • Fenton-like composite catalyst as well as preparation method and application thereof

    CN122352269A

  • Three-dimensional ordered macroporous high-entropy oxide material and preparation method and application thereof

    CN122916237A